The Analysis of Performance of State Civil Apparatus at The Regional Financial and Assets Management Agency of Supiori District - Hermanu Iriawan; Diah Novita Sari; Samsiah Samsiah (Universitas Negeri Makassar, 2021)
In facing the era of globalization which is full of challenges and opportunities, state apparatus as public servants who provide the best service towards good governance. This study uses a qualitative approach. With observation data collection techniques and in-depth interviews. This study aims to analyze the performance of the State Civil Apparatus at the Regional Financial and Asset Management Agency of Supiori Regency. This study aims to determine and analyze the performance of the State Civil Apparatus at the Regional Financial and Asset Management Agency of Supiori Regency and to identify and analyze the supporting and inhibiting factors of the performance of the State Civil Apparatus at the Regional Financial and Asset Management Agency of Supiori Regency. The results showed that the performance of financial and asset managers in the Supiori district was still in the